STRENGHTENING PERFORMANCE OF INDONESIAN NATIONAL POLICE IN SOUTH SUMATERA REGIONAL POLICE - Mayastinasari, Vita; Suseno, Bayu (UI Scholars Hub, 2020)
Excellent police service is very important. Community expected the excellent police service, so that the National Police needs to create positive performance. The study aims to determine whether there is a direct or indirect effect of reward and job satisfaction on performance and strengthening the performance of the National Police. The research method is a survey with path analysis. The research variables are 2 exogenous variables, reward system (X1) and job satisfaction (X2) and 1 endogenous variable, performance (X3). Sampling of 548 Polri personnel in the South Sumatra Regional Police used stratified random sampling. Based on the results of statistical calculations, there is a positive direct effect of rewards on performance with a path coefficient of 0.381 and a T-count of 10.217. Job satisfaction on performance has a positive direct effect with a path coefficient of 0.475; T-count value of 12.740. The positive direct effect of rewards on job satisfaction with a path coefficient of 0.714 and the T-count of 23.817 and the indirect effect of rewards on performance through job satisfaction has a path coefficient of 0.339; T-count value is 11,242. Strengthening the performance of the National Police is done by building a healthy job environment through the accuracy of the management of reward, based on the accuracy of performance assessment instruments, so that it has an impact on job satisfaction and has positive effect on performance.